Community Policing as a Crime Prevention Strategy in Urban Areas - Yaqzhan, Althafandhika; Daniswara, Prasna; Utomo, Wisnu (Indonesian National Police Academy, 2025)
Urban areas are highly complex. This complexity leads to high crime rates in some urban areas. Crime in urban areas is caused by deep-rooted problems. To overcome this, solutions that address the root causes are also needed. Using a community policing approach, this study will demonstrate methods for preventing crime in urban areas. The study aims to analyze how community policing works to address crime in urban areas. It employs a literature review method, utilizing data from documents, journals, books, and relevant official reports related to the topic. The findings show that crime in urban areas often occurs only in certain areas with specific characteristics. By understanding this, it will be more effective to formulate a community policing-based approach to the community.